Modeling the anisotropy of hot plastic deformation of two-phase titanium alloys with a colony microstructure - Fan, X.G.; Jiang, X.Q.; Zeng, X.; Shi, Y.G.; Gao, P.F.; Zhan, M. (International journal of plasticity, 2018)
Two-phase titanium alloys deform heterogeneously in primary hot working due to the strong anisotropy of plastic deformation of colony structure associated with the transformation crystal structure, morphology and orientation relationship between the constituent phases. To understand the heterogeneous deformation in primary hot working, a homogenized crystal plasticity constitutive model is developed for a single colony which relates anisotropic deformation behavior to microstructural features. Efforts are made to model the morphological effects which cause the abnormally low measured critical resolved shear stress (CRSS) of two basal slip systems and the anisotropic Hall-Petch strengthening associated with the Burgers orientation relationship. The model is able to capture the deformation characteristics and texture evolution in compression of colony structure. It is found that the morphological effects cause the formation of transverse texture and continuous flow softening in hot compression. •A homogenized CP model for colony structure is developed to relate the plastic anisotropy to microstructural features.•Morphological effects on plastic anisotropy are revealed and modeled.•A unified model for anisotropy in Hall-Petch strengthening is proposed.•Morphological effects are important to the formation of transverse texture in hot compression.